Meta Analisis Pengaruh Media Pembelajaran Terhadap Hasil Belajar Fisika Peserta Didik - Misnawati Misnawati; Abdul Salam; Surya Haryandi (Indonesian Publication Center, 2022)
This meta-analysis evaluates the effectiveness of instructional media on students' physics learning outcomes based on 51 primary national and international studies (2012–2021). The results demonstrate that the application of instructional media exerts a positive and effective overall influence, with an effect size (ES) of 1.019, categorized as a large effect. These findings are consistent across all educational levels (higher education, senior high, and junior high), which all fall within the large effect category. Regarding physics topics, the majority of the 28 analyzed topics show a large effect, while others are classified as moderate or small. Furthermore, 6 out of 7 types of learning outcomes, as well as 17 out of 28 types of media analyzed, demonstrate large effect sizes. This study suggests that future research should incorporate a larger number of primary studies to achieve more precise and comprehensive analytical results.